2014
DOI: 10.1186/1752-4458-8-26
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards people with mental illness among psychiatrists, psychiatric nurses, involved family members and the general population in a large city in Guangzhou, China

Abstract: PurposeStigma towards people with mental illness is believed to be widespread in low and middle income countries.MethodsThis study assessed the attitudes towards people with mental illness among psychiatrists, psychiatric nurses, involved family members of patients in a psychiatric facility and the general public using a standard 43-item survey (N = 535). Exploratory factor analysis identified four distinctive attitudes which were then compared using Analysis of Covariance (ANCOVA) among the four groups, all w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
0
25
1
1
Order By: Relevance
“…Many studies showed that attitudes about mental illness are clearly linked to various demographic variables such as age and education (26,27,28) , The current study found that there is no correlation between the attitudes of students and demographic variables of age and parent's education. As well there is no statistically significant differences were detected between the medical and non-medical students regarding their age, residence and mother's education which support the homogeneity of the study sample.…”
Section: Discussioncontrasting
confidence: 60%
“…Many studies showed that attitudes about mental illness are clearly linked to various demographic variables such as age and education (26,27,28) , The current study found that there is no correlation between the attitudes of students and demographic variables of age and parent's education. As well there is no statistically significant differences were detected between the medical and non-medical students regarding their age, residence and mother's education which support the homogeneity of the study sample.…”
Section: Discussioncontrasting
confidence: 60%
“…This instrument has been used initially in several settings in Nigeria (Iheanacho et al, 2014), China (Sun et al, 2014), and the United States (Chiles et al, under review).…”
Section: Social Acceptancementioning
confidence: 99%
“…Previous researchers studied attitude towards people with mental illness among clergy (Igbinomwanhia, James, & Omoaregba, 2013); medical students (Altindag, Yanik, Ucok, Alptekin, & Ozkan, 2006;Elizur & Rosenheim, 1982 undergraduates (Shruti, Singh, & Kataria, 2016); general public (Yuan, Abdin, Picco, Vaingankar, Shahwan, Jeyagurunathan, & Subramaniam, 2016); psychiatrict/psychiatric nurses (Sun, Fan, Nie, Zhang, Huang, He, & Rosenheck, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Attitude towards people with mental illness is studied in many regions of the world such as Chicago (Watson, Corrigan, & Ottati, 2004); China (Sun, Fan, Nie, Zhang, Huang, He, & Rosenheck, 2014); Hong Kong (China) (Todor, 2013); India (Poreddi, Thimmaiah, & Math, 2015); Israel (Kimhi, Barak, Gutman, Melamed, Zohar, & Barak, 1998); Saudi Arabia (Amira, 2016 (Igbinomwanhia, James, & Omoaregba, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%